2018
DOI: 10.4172/2157-7439.1000494
|View full text |Cite
|
Sign up to set email alerts
|

Platanus orientalis Leaf Mediated Rapid Synthesis of Catalytic Gold and Silver Nanoparticles

Abstract: This report details on synthesis of AuNPs and AgNPs using POLE with optimized reaction parameters, for the first time. The bioreduced nanoparticles were characterized using UV-visible spectroscopy, high resolution transmission electron microscopy (HRTEM), energy dispersive spectroscopy (EDS), dynamic light scattering (DLS), X-ray diffraction spectroscopy (XRD), fourier transform infrared (FTIR) spectrometry. Both AuNPs and AgNPs Further we evaluated the catalytic potential of the nanoparticles towards reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…This signifies that LFLE requires lower concentration of AgNO 3 as compared to other phytogenic routes and hence is more economical as well. On the other hand 1 mM and 2 mM of HAuCl 4 were found to be suitable for synthesis of AuNPs which is identical to the synthesis reported using extracts of Litchi chinensis and Platanus orientalis ( Shende et al, 2017 ; Shende et al, 2018 ). It should be noted that reaction time can be remarkably shortened by increasing higher concentration of the metal ions if the quantity of the reducing phytochemicals in plant extract is not sufficiently high.…”
Section: Resultssupporting
confidence: 81%
“…This signifies that LFLE requires lower concentration of AgNO 3 as compared to other phytogenic routes and hence is more economical as well. On the other hand 1 mM and 2 mM of HAuCl 4 were found to be suitable for synthesis of AuNPs which is identical to the synthesis reported using extracts of Litchi chinensis and Platanus orientalis ( Shende et al, 2017 ; Shende et al, 2018 ). It should be noted that reaction time can be remarkably shortened by increasing higher concentration of the metal ions if the quantity of the reducing phytochemicals in plant extract is not sufficiently high.…”
Section: Resultssupporting
confidence: 81%
“…Compared to other reports, the AuNP–film catalyst in this work showed higher catalytic activity for the reduction of 4-NP to 4-AP which was 10 times (0.199 × 10 −2 min −1 ) and 4 times (0.45 × 10 −2 min −1 ) higher than for AuNPs prepared from Gnida glauca leaf and stem extracts [45]. Another report by Shende et al [4647] demonstrated that AuNPs prepared from Litchi Chinensis peel extract and Platanus Orientalis leaf extract showed 1000 times lower catalytic activity with rate constants of 0.00136 × 10 −2 and 0.00191 × 10 −2 min −1 . Hence, the AuNP–film catalyst in the nanocomposite of this work shows the importance of mesoporous silica as a framework for growing AuNPs in the silicate nanochannels with higher ordered nanostructure.…”
Section: Resultsmentioning
confidence: 52%
“…Various physical and chemical biological methods have been employed to synthesize AgNPs with well-defined sizes and shapes. Similarly, the synthesis of biocompatible AgNPs was reported using bacteria, fungi, algae and medicinal plants [72][73][74][75]. Thus, the incorporation of nanostructured silver and their alloys into scaffolds at sub lethal dosages can enhance the shelf life of the material and possibly prevent post-operative pathogenic infections [76,77].…”
Section: Silvermentioning
confidence: 99%